2004
DOI: 10.1136/jcp.2004.016634
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of human papillomavirus DNA in head and neck cancers and papillomas

Abstract: Aim: To determine the prevalence, type, physical state, and viral load of human papillomavirus (HPV) DNA in cases of head and neck cancer and recurrent respiratory papillomatosis (RRP). Methods: The prevalence and type of HPV DNA was determined in 27 fresh frozen tissue specimens from patients with head and neck cancers and 16 specimens from 10 patients with RRP by MY09/MY11 and GP5+/ GP6+ nested polymerase chain reaction (PCR) and subsequent restriction enzyme cleavage. The physical state of HPV DNA was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 26 publications
2
49
1
2
Order By: Relevance
“…Of the 14 papillomas evaluated by Fregonesi et al (14) using in situ hybridization, 14% (2) were positive for HPV 6/11, 22% (n = 3) were positive for HPV 16/18, and the great majority (64%, 9) were negative for HPV. However, Major et al (16) found 100% PCR positivity for HPV 6 or HPV 11 DNA in 10 papillomas due to recurrent respiratory papillomatosis. Generally, in children with laryngeal papillomatosis, there can be coinfection by HPVs 6 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 papillomas evaluated by Fregonesi et al (14) using in situ hybridization, 14% (2) were positive for HPV 6/11, 22% (n = 3) were positive for HPV 16/18, and the great majority (64%, 9) were negative for HPV. However, Major et al (16) found 100% PCR positivity for HPV 6 or HPV 11 DNA in 10 papillomas due to recurrent respiratory papillomatosis. Generally, in children with laryngeal papillomatosis, there can be coinfection by HPVs 6 and 11.…”
Section: Discussionmentioning
confidence: 99%
“…The squamous papilloma is associated with human papilloma virus (HPV) types 6, and 11 (Major et al, 2005). Oral squamous papilloma, including the vermilion portion of the lip, is the most common papillary lesion of the oral mucosa and makes up approximately 2.5% of all oral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to oral carcinomas, a greater diversity of other HPV types has been detected: HPV18, HPV26, HPV31, HPV33, HPV39, HPV36, HPV45, HPV51, HPV52, HPV58, HPV59, HPV66, and HPV69 [8,9,14,20,26,29,39,65,71,90,94]. Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94].…”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%